Efecto combinado del control de malezas y la nutrición foliar orgánica en el cultivo de arroz (oryza sativa l.) de secano - Heredia Martínez, Daniel Vicente (2011)
The present investigation work, was carried out during the months of January to May of the 2010, in Riego CEDEGE'S Project, Rcto White Stick", parish Febres Cordero, canton Babahoyo, County of The Rivers, with coordinated geographical 4403 ' of south latitude and 79032 ' of longitude west and an elevation of 8 m.s.n.m. The place presents a climate humid tropical type, the annual half temperature of 25.60C., precipitation of 2329.8mm., relative humidity of 82%. As genetic material of siembra it was used certified seeds of the variety of rice INIAP 15", obtained by the National Institute of Agricultural Investigations. The treatments were evaluated with the help of Bispiribac sodium + Pyrazosulfuron and Fertilizantes Foliares in different dose. The design denominated Complete Blocks was used at random with 5 treatments and three repetitions. The variables to evaluate were subjected to the variancia analysis, and the test of statistical significancia was used from Tukey to 95% of probabilities.